2017
DOI: 10.1037/law0000114
|View full text |Cite
|
Sign up to set email alerts
|

Redundant deliberation about negative consequences: Decision inertia in emergency responders.

Abstract: Major emergencies are high-stakes, ambiguous, dynamic and stressful events. Emergency response commanders rely on their expertise and training to mitigate these factors and implement action. The Critical Decision Method was used to interview n=31 commanders from the Police (n=12), Fire and Rescue (n=15) and Ambulance Services (n=4) in the UK about challenges to decision making. Transcripts were analysed in two ways: (i) using thematic analyses to categorise the challenges to incident command; and (ii) grounded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 73 publications
1
67
0
Order By: Relevance
“…The authors recommended that interventions to reduce Running head: EXTREME TEAMS AND MAJOR EMERGENCIES 9 uncertainty in high-risk environments should specifically target exogenous challenges, which might in turn reduce inherent endogenous challenges. In a second study, the authors used cognitive interviews to explore exogenous challenges in emergency teams and found that uncertainty was related to four sources: trust issues, competition, poor role understanding and communication (Power & Alison, 2017a). Although more research is needed to comprehensively identify the challenges to emergency teamwork, these challenges provide a starting point that will be used in this paper to integrate research on emergency teamwork within the existing team processing framework (e.g., Wilson et al, 2015).…”
Section: Teamwork During Emergencies: What We Know So Farmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors recommended that interventions to reduce Running head: EXTREME TEAMS AND MAJOR EMERGENCIES 9 uncertainty in high-risk environments should specifically target exogenous challenges, which might in turn reduce inherent endogenous challenges. In a second study, the authors used cognitive interviews to explore exogenous challenges in emergency teams and found that uncertainty was related to four sources: trust issues, competition, poor role understanding and communication (Power & Alison, 2017a). Although more research is needed to comprehensively identify the challenges to emergency teamwork, these challenges provide a starting point that will be used in this paper to integrate research on emergency teamwork within the existing team processing framework (e.g., Wilson et al, 2015).…”
Section: Teamwork During Emergencies: What We Know So Farmentioning
confidence: 99%
“…However, cooperation is uniquely challenged as emergency teams are often temporary and dynamic, meaning that team members rotate and are unfamiliar at an interpersonal level. Related to cooperation, Power and Alison (2017a) identified two challenges to emergency teamwork: (i) trust issues; and (ii) competition between team members. They suggest that these challenges impeded cooperation as they reduced team members' motivation to work together.…”
Section: Cooperation During Emergenciesmentioning
confidence: 99%
See 2 more Smart Citations
“…With regards to methods this is largely due to the fact that the majority of current methodological approaches are directed at measuring the presence of a given behaviour rather than the possible processes underpinning non-behaviour. Unlike decision avoidance, which describes inaction as a result of suspended disengagement with decision processing, decision inertia reflects behavioural inaction despite cognitive processing, and has been observed in the context of critical incidents (e.g., Power & Alison, 2017). Decision inertia is characterised by redundant deliberation; the constant rumination over possible choices in the absence of further useful information.…”
mentioning
confidence: 99%